Pengaruh Beauty Vlogger Terhadap Perilaku Konsumtif Siswa Di SMP Negeri 3 Kabanjahe Tahun 2023 - Widodo Widodo (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
This research aims to determine the influence of beauty vloggers on the consumer behavior of students at SMP Negeri 3 Kabanjahe. The formulation of the problem in this research is what influence beauty vloggers have on the consumer behavior of students at SMP Negeri 3 Kabanjahe. This research uses quantitative research methods with a survey approach. The sample in this study consisted of 100 students who had the criteria of having watched beauty vlogger vlogs or beauty tutorials. The data collection tool in this research uses instruments in the form of questionnaires, namely the beauty vlogger questionnaire and the consumer behavior questionnaire. The results of the research show that there is an influence of beauty vloggers on the consumer behavior of students at SMP Negeri 3 Kabanjahe.